2020
DOI: 10.1101/2020.05.07.20094151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The British Thoracic Society survey of rehabilitation to support recovery of the Post Covid-19 population

Abstract: Objectives Those discharged from hospital after treatment for Covid-19 are likely to have significant and ongoing symptoms, functional impairment and psychological disturbances. There is an immediate need to develop a safe and efficient discharge process and recovery programme. Pulmonary rehabilitation is well placed to deliver a rehabilitation programme for this group but will most likely need to be adapted for the post Covid-19 population. The purpose of this survey was to rapidly identify the components of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…The impact of CC on respiratory infectious diseases has recently raised an increasing research interest, particularly in children affected by chronic respiratory diseases [4].…”
Section: The Impact Of Climate Change On Paediatric Respiratory Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of CC on respiratory infectious diseases has recently raised an increasing research interest, particularly in children affected by chronic respiratory diseases [4].…”
Section: The Impact Of Climate Change On Paediatric Respiratory Infecmentioning
confidence: 99%
“…In March 2020, the British Thoracic Society released the position statement, "The Environment and Lung Health 2020" [4], warning on the upcoming risks of people with chronic respiratory diseases who may be particularly sensitive to the impacts of CC.…”
Section: Introductionmentioning
confidence: 99%
“…Just like the RECOVERY program design, the clinics should cater to all the categories of COVID-recovered patients, mild, moderate or severe, and will be key components of hospitals in the coming years of post-pandemic era. [13,14] It has also been recommended that post-COVID-19 recovery, patients should lead a healthy lifestyle, have nutritious foods to enhance immunity and do regular physical activity, breathing exercises or yoga. [3] Likewise, HCW, in our survey, post-recovery was focussed on a nutritious diet (71%) and a majority (65%) were practising some form of physical activity, which was in tune with the recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence for the efficacy of pulmonary rehabilitation (PR) for people with chronic respiratory disease [1] and previous literature has also demonstrated the benefits of PR in terms of improvements in exercise capacity and quality of life in survivors of adult respiratory distress syndrome and influenza A (H1N1) pneumonitis [2]. International statements have now suggested that the PR setting may be an appropriate rehabilitation pathway for patients recovering from COVID-19 who have persistent pulmonary and extra-pulmonary symptoms and functional limitations [2][3][4][5]. In Sydney, Australia, the Northern Sydney Local Health District (NSLHD) has had 550 cases of COVID-19 (as of 15 July 2020).…”
Section: Introductionmentioning
confidence: 99%